Evidence for the temperature-mitigating capacity of urban blue space – a health geographic perspective - Völker, Sebastian; Baumeister, Hendrik; Claßen, Thomas; Hornberg, Claudia; Kistemann, Thomas (ERDKUNDE, 2013)
Climate change is regarded as one of the greatest challenges to cities in the future. Some proposals focus on incorporating urban green space to counter the rise in temperature and ensuing public health hazards. Urban blue spaces, defined as all surface waters within a city, are regarded as a possible factor for temperature mitigation, but effects have not been quantified and so remain underrepresented in research, recommendations for action and planning. A systematic review was conducted of studies quantifying the temperature-mitigating effects of urban blue compared to other urban sites (n=27). The studies included in the review measured air temperatures at various types of urban blue space such as ponds, lakes or rivers and compared them with reference sites at defined distances or to urban reference sites in the same city. The meta-analysis suggested that a cooling effect of 2.5 K (CI 95% 1.9-3.2 K, p<0.01) during the warmest months on northern hemisphere (between May and October) can be attributed to urban blue sites when including remote sensing data. However, research on the air temperature effects of urban blue space remains sparse compared to studies on urban green. The cooling effects clearly attributable to urban blue space are limited by surrounding environmental conditions like microclimate, urban development, wind velocity, wind turbulence, wind direction, temperature and humidity. Future research is needed to help planners use urban blue space efficiently as a temperature-mitigating and health protecting and promoting factor. The temperature-mitigating capacity of urban blue can potentially reduce heat stress in urban areas. To create healthy environments in the cities of the future, a better understanding of health affecting aspects of urban blue is needed to initiate public health action.